2021
DOI: 10.31224/osf.io/6rgtz
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Water Quality Index (WQI) for Evaluation of the Surface Water Quality of Bangladesh and Prediction of WQI from Limited Parameters

Abstract: Healthy aquatic environment is crucial for preserving aquatic lives in surface waters. Increasing industrial or agricultural discharge or run-off can pollute water leading to unhealthy aquatic environment causing distress in fishes and other aquatic lives. In places with lack of infrastructure and regulatory enforcement, pollution can be particularly challenging to handle. Assignment of an indexing system can be helpful for analyzing pollution pattern in the polluted rivers which can be helpful for remediation… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…the study [28] also identified the tannery effluent-modulated sample BOD, which was reported as 20.8-40 mg/L for 5-100% samples. Mallick et al [51]denoted the value >3mg/L, therefore our findings could potentially indicate the deteriorating condition of water quality in the river.…”
Section: Comparison Among Chemical and Biochemical Contaminants And S...mentioning
confidence: 52%
“…the study [28] also identified the tannery effluent-modulated sample BOD, which was reported as 20.8-40 mg/L for 5-100% samples. Mallick et al [51]denoted the value >3mg/L, therefore our findings could potentially indicate the deteriorating condition of water quality in the river.…”
Section: Comparison Among Chemical and Biochemical Contaminants And S...mentioning
confidence: 52%